Verbal Language Method Application in Effort of Increasing the Communicating Capability of Hearing-Impaired Child of Early Age From 6-7 Years Old - Putri, Ni Luh (Universitas Negeri Semarang, 2014)
This research aims to increase communicating capability of hearing-impaired child of early age through verbal language method. This research was implemented at Poyowa Besar Primary School of Special Needs at Kotamobagu City. The research method used in this research was action research. The conclusion of this research result was that there was an increase of communicating capability on two hearing-impaired children researched at cycle I, it obtained outcome percentage of 10 %, at cycle II, it obtained 20%, and at cycle III, there was 80%. Based on that analysis result data, it says that percentage of preliminary research from cycle I, to cycle II, and cycle III underwent the increase.How to citePutri, N. (2014). Verbal Language Method Application in Effort of Increasing the Communicating Capability of Hearing-Impaired Child of Early Age From 6-7 Years Old. Indonesian Journal Of Early Childhood Education Studies, 3(1), 14-17. doi:10.15294/ijeces.v3i1.9470